2001
DOI: 10.1016/s0014-5793(01)02434-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and production of genetically modified soybean protein with anti‐hypertensive activity by incorporating potent analogue of ovokinin(2–7)

Abstract: The potent anti-hypertensive peptide, RPLKPW, has been designed based on the structure of ovokinin(2^7). The sequence encoding this peptide was introduced into three homologous sites in the gene for soybean L L-conglycinin K KP P subunit. The native K KP P subunit as well as the modified, RPLKPW-containing K KP P subunit were expressed in Escherichia coli, recovered from the soluble fraction and then purified by ion-exchange chromatography. The RPLKPW peptide was released from recombinant RPLKPW-containing K K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…12,13) However, this study is the first report on the improvement of bile acidbinding ability of glycinin by the incorporation of the VAWWMY sequence.…”
mentioning
confidence: 87%
“…12,13) However, this study is the first report on the improvement of bile acidbinding ability of glycinin by the incorporation of the VAWWMY sequence.…”
mentioning
confidence: 87%
“…This modification allowed the RPLKPW sequences to be released by trypsin and chymotrypsin. Matoba et al 6) and Yamada et al 14) have designed soybean -conglycinin 0 subunit containing RPLKPW and confirmed that the introduced bioactive peptides were released by the action of trypsin and chymotrypsin and elicited high anti-hypertensive activity in vivo. These results suggest that RPLKPW could also be released from the modified versions of A3B4 by the action of trypsin and chymotrypsin and may exhibit high anti-hypertensive activity in vivo, since the positions of the modifications are in the disordered region on the molecular surface.…”
mentioning
confidence: 94%
“…We also constructed expression plasmids for modified versions of A3B4. The DNA regions for two RPLKPW (strong anti-hypertensive peptide) 6) -like sequences of TPSYPP and RPSHGK corresponding to residues 268-273 and 275-280 of the hypervariable region in the A3B4 subunit were respectively changed to the DNA sequences for * Present address: Laboratory of Applied Molecular Design, Marine Biotechnology Institute, Kamaishi, Iwate 026-0001, Japan y To whom correspondence should be addressed. Fax: +81-774-38-3761; E-mail: sutsumi@kais.kyoto-u.ac.jp Biosci.…”
mentioning
confidence: 99%
“…SBP was measured with an indirect tail-cuff method by using MK-2000 (Muromachi Kikai Co. Ltd, Tokyo, Japan), as we [11] and others [20,21] described and validated. At 8 and 16 weeks of age (wks), SBP was measured at least five times in conscious mice (n=8-16 for each group).…”
Section: Measurement Of Systolic Blood Pressure (Sbp)mentioning
confidence: 99%